Peran Uni Eropa Dalam Demokratisasi Di Republik Ceko Pasca Revolusi Beludru (2000-2007) - Satria Whisnu Murti ; Muharjono Muharjono (Jurnal Paradigma, 2016)
The European Union is an International Governmental Organization that has power to regulate and guide the member countries and has a role as an instrument, arena and actor. That power is channeled through international agreements and technical assistance principled democracy. The expansion of EU in uence in the Central European region began in the 1990s. In 1993 the Czech Republic and Slovakia split off, this phenomenon is called the Velvet Revolution. This revolution marked the collapse of the communist regime’s in uence in the Czech Republic. Vaclav Havel as the rst president of the Czech Republic decided to reform the country become more democratic. In early 2000 the EU channel values and principles of democracy in the Czech Republic through the Copenhagen Criteria and the Europe Agreement as well as support the implementation of this agreement through the nancial assistance program, called Phare Program and the Special Accession Program for Agricultural and Rural Developments. The European Union is an actor who played an important role in the process of change in the Czech Republic towards democracy.